RATIONALITY FOR CONSISTENT RETURN IN IHSG INVESTING - Chandra, Herry
The stock market provided one of the highest return among all investment classes like properties, government bond, investment grade cooperate bonds and bank deposit. In past decade, the IHSG provided Compound Annual Growth Rate return of 7.2% and the LQ45 index provide return of 4.5%. However, some investor believe that one can achieve higher return by performing individual stock picking and not investing in the ETF that track the index market. Some investor buying the stock based on the fundamental value about the company like Price Book Value, Price Earning Ratio, Return on Equality and market cap. This study aiming to check if there are ratio that can consistently provide higher return than the index and what financial ratio that provided the highest stock return in the period of 2008 to 2019.